Analysis of Length Work and Visibility on Online Learning Toward Teachers Fatigue at Junior High School 2 Durenan District Trenggalek - Yusril Ihzayahya; Ardi Bastian (Universitas STRADA Indonesia, 2021)
Eye fatigue is a complaint that is often found because of the interaction of the eye with the continuous use of screens. Frequent viewing of screens can make eyes tired. Radiation can also be detrimental to health. The purpose of this research was to analyze length of work and visibility in online learning against eye fatigue of teachers at Junior High School 2 Durenan District Trenggalek.The research design was an observational quantitative study with a cross sectional approach with the focus of the research being aimed at analyzing the effect of length of work and visibility on online learning on teacher eye fatigue at Junior High School 2 Durenan District Trenggalek with a population of 40 respondents and a sample of 35 respondents who were drawn by the simple random sampling technique. The findings show that Most of the respondents have long worked in the old category as many as 23 respondents (65.7%). Most of the respondents have eye distance in the near category as many as 19 respondents (54.3%). Most of the respondents experienced complaints of eye fatigue as many as 22 respondents (62.9%). The results of the study used Multiple linear regression shows that with a p-value of 0.000 <0.05, H1 is accepted, so it can be concluded that simultaneously it exists the effect of length of work and visibility on online learning on eye fatigue of teachers at Junior High School 2 Durenan District Trenggalek with a magnitude of the effect of 72.7%. It is expected that the respondent should limit the minimum distance between the eyes and the screen, namely by arranging the chair as comfortable as possible and positioning the back upright so that it does not appear too close to the screen. In addition, it is also recommended to wear anti-radiation glasses in order to maximize performance.